(untitled) (International Journal of Nursing Education, 2021)
Purpose: This research aims to understand the perceptions of impact of spirituality towards pandemic COVID-19 from the perspective of the older adults, explores the themes of such perception older adults regarding spirituality in the pandemic COVID-19. Methods: This research is based on qualitative research in a phenomenological methodology. The research participants included older adults aged 60-90 living at home in Malang, Jawa Timur Provinces, Indonesia. Data collection methodologies included in-depth interviews and observation of participants. The data were analyzed in the phenomenological methodology by Colaizzi. Results: As a result of the research, it was found that all significant statements about the Indonesian older adults perception of spirituality in the pandemic COVID-19 fell within 10 categories with 2 major themes and 3 minor themes. The 2 major themes were: The COVID-19 pandemic is coming to an end and Spiritual improvement of the older adults. Conclusion: This study provides factor –factor to use on foundation to achieve spiritual need of older adults in the pandemic COVID-19.